2017
DOI: 10.1155/2017/5601593
|View full text |Cite
|
Sign up to set email alerts
|

ROS: Crucial Intermediators in the Pathogenesis of Intervertebral Disc Degeneration

Abstract: Excessive reactive oxygen species (ROS) generation in degenerative intervertebral disc (IVD) indicates the contribution of oxidative stress to IVD degeneration (IDD), giving a novel insight into the pathogenesis of IDD. ROS are crucial intermediators in the signaling network of disc cells. They regulate the matrix metabolism, proinflammatory phenotype, apoptosis, autophagy, and senescence of disc cells. Oxidative stress not only reinforces matrix degradation and inflammation, but also promotes the decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
284
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(292 citation statements)
references
References 109 publications
(160 reference statements)
7
284
0
1
Order By: Relevance
“…According to the free-radical theory of aging, oxidative stress initiated by ROS accumulation contributes to the functional decline that occurs during aging [8]. Generally, ROSs include the superoxide anion (O 2− ), nitric oxide (NO), and hydroxyl radicals (OH), which are byproducts of cell oxidative metabolism [29]. Once the intracellular ROS accumulation has exceeded the cell's capacity to scavenge, it can lead to oxidative damage and concomitant cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…According to the free-radical theory of aging, oxidative stress initiated by ROS accumulation contributes to the functional decline that occurs during aging [8]. Generally, ROSs include the superoxide anion (O 2− ), nitric oxide (NO), and hydroxyl radicals (OH), which are byproducts of cell oxidative metabolism [29]. Once the intracellular ROS accumulation has exceeded the cell's capacity to scavenge, it can lead to oxidative damage and concomitant cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…As a common trigger of oxidative stress in vitro, H 2 O 2 has been widely applied to investigate the underlying mechanisms in IVD cells death. Currently, it have been confirmed that apoptosis and autophagy participate in the H 2 O 2 ‐induced NP cell death . Nevertheless, there have been few studies about programmed necrosis or exploration of the relevant mechanisms in IVDD.…”
mentioning
confidence: 99%
“…131 ROS is detrimental to the structural and functional homeostasis of the disc by causing the damage of lipids, DNA, and proteins. 132 Hydrogen peroxide, identified in human NP tissue, along with peroxisomes detected in AF cells in vitro, further support discs cells as ROS generators. 133,134 With mitochondrion dysfunction as a known source of excessive ROS production, the role of mitochondrion-dependent ROS has been described in various disc cells including human and rat NP and AF cells.…”
Section: Oxidative Stress and Deregulated Signalingmentioning
confidence: 76%